A FAST FRACTIONAL DIFFERENCE ALGORITHM. (20th May 2014) - Jensen, Andreas Noack; Nielsen, Morten Ørregaard
Abstract We provide a fast algorithm for calculating the fractional difference of a time series. In standard implementations, the calculation speed (number of arithmetic operations) is of order T2, where T is the length of the time series. Our algorithm allows calculation speed of order TlogT. For moderate and large sample sizes, the difference in computation time is substantial. Copyright © 2014 John Wiley & Sons, Ltd.